Zearalenone: A Mycotoxin With Different Toxic Effect in Domestic and Laboratory Animals’ Granulosa Cells - Zhang, Guo-Liang; Feng, Yu-Long; Song, Jun-Lin; Zhou, Xiang-Shan (Frontiers in Genetics, 2018)
Zearalenone (ZEA), one of the most prevalent estrogenic mycotoxins, is mainly produced by Fusarium fungi and has been proven to affect the reproductive capacity of animals. Exposure of farm animals to ZEA is of public concern globally because of its toxicity and wide distribution in feeds. In vitro and in vivo experiments indicate that ZEA possesses estrogenic activity in mice, swine, Equus asinus, and cattle. The precise mechanism of the reproductive toxicity of ZEA has not been established yet. This article reviews evidence on the deleterious effects of ZEA on mammalian folliculogenesis from early to final oogenesis stages. Such effects include impaired granulosa cell (GC) development and follicle steroidogenesis, reduced oocyte nest breakdown, damaged meiotic progression, poor fetal oocyte survival, accelerated primordial follicle activation, , and enhanced follicle atresia. These phenomena may result in reproductive and non-reproductive problems in domestic animals. In addition, emerging data indicate that ZEA may cause mRNA expression changes in GCs. In general, E. asinus is more sensitive than swine to ZEA exposure. Finally, results of in vivo animal studies and in vitro tests are reported and discussed.